Metabolic control of immune tolerance in health and autoimmunity. Issue 5 (October 2016) - Carbone, Fortunata; La Rocca, Claudia; De Candia, Paola; Procaccini, Claudio; Colamatteo, Alessandra; Micillo, Teresa; De Rosa, Veronica; Matarese, Giuseppe
Highlights: Adipose tissue controls immune functions through secretion of adipokines. Obesity represents a risk factor for autoimmunity. Malnutrition increases the susceptibility to infections. Caloric restriction improves the clinical course of several autoimmune diseases. Autoimmunity associates with an altered metabolism. Abstract: The filed that links immunity and metabolism is rapidly expanding. The adipose tissue, by secreting a series of immune regulators called adipokines, represents the common mediator linking metabolic processes and immune system functions. The dysregulation of adipokine secretion, occurring in obese individuals or in conditions of malnutrition or dietary restriction, affects the activity of immune cells resulting in inflammatory autoimmune responses or increased susceptibility to infectious diseases. Alterations of cell metabolism that characterize several autoimmune diseases strongly support the idea that the immune tolerance is also regulated by metabolic pathways. The comprehension of the molecular mechanisms underlying these alterations may lead to the development of novel therapeutic strategies to control immune cell differentiation and function in conditions of autoimmunity.